Statistical Tests for MIXMAX Pseudorandom Number Generator - Narek H. Martirosyan; Gevorg A. Karyan; Norayr Z. Akopov (Изд-во НАН РА)
The Pseudo-Random Number Generators (PRNGs) are key tools in Monte Carlo simulations. More recently, the MIXMAX PRNG has been included in ROOT and Class Library for High Energy Physics (CLHEP) software packages and claims to be a state of the art generator due to its long period, high performance and good statistical properties. In this paper the various statistical tests for MIXMAX are performed. The results compared with those obtained from other PRNGs, e.g., Mersenne Twister, Ranlux, LCG reveal better qualities for MIXMAX in generating random numbers. The Mersenne Twister is by far the most widely used PRNG in many software packages including packages in High Energy Physics (HEP), however, the results show that MIXMAX is not inferior to Mersenne Twister.
Keywords: Mathematics; Computer software; Algorithm